RESPON DUA NOMOR HARAPAN PIRETRUM TERHADAP PEMUPUKAN - Muhamad Djazuli (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
Responses of two promising clones of pyrethrum to fertilizer applicationPyrethrum is one of the potential botani-cal pesticides to be further developed for the substitution of synthetic pesticide such as pyreth-roid, which is found to be harmful both to the environment and human being. Therefore, high yielding plant material with high pyrethrin content is a prerequisite for a continuous supply of raw material in botanical pesticides produc-tion. For that purpose, two promising clones of pyrethrum were assessed for their response to fertilizer application and conducted at Kayu Giyang village (1500 m asl) of  Wonosobo re-gency, Central Java. Two promising clones of pyrethrum namely Prau 6 and Gunung Wates 45 were subjected to seven NPK fertilizer combina-tion treatments using Split Plot Design with three replications. The results showed that N and P fertilizer applications at the Kayu Giyang, Dieng highland were able in improving produc-tivity of pyrethrum by increasing flower number and flower fresh weight of both Prau 6 and Gunung Wates 45 clones, significantly. NPK application with medium dosage (100 kg N, 200 kg P, and 100 kg K/ha) was able to produce high productivity and fertilizer efficiency. However, there was no significant effect as compared to the high dosage application. Based on the nut-rient status and dry weight, it could be con-cluded that amount of N absorbed by plant was high, followed by K and P. Furthermore, based on the nutrient status, the P fertilizer absorbed by pyrethrum was relatively low and approxi-mately 20.00% from N absorbed. The pyrethrin contents from the two clones tested were relatively high (>1.00%).